2019
DOI: 10.3390/nu11092077
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance and Impact of Millet-Based Mid-Day Meal on the Nutritional Status of Adolescent School Going Children in a Peri Urban Region of Karnataka State in India

Abstract: The study assessed the potential for use of millets in mid-day school meal programs for better nutritional outcomes of children in a peri-urban region of Karnataka, India, where children conventionally consumed a fortified rice-based mid-day meal. For a three-month period, millet-based mid-day meals were fed to 1500 adolescent children at two schools, of which 136 were studied as the intervention group and were compared with 107 other children in two other schools that did not receive the intervention. The int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 19 publications
1
48
0
Order By: Relevance
“…Consumption of little millet could potentially contribute up to 28% Fe, 36.8% Zn, and 27.4% protein of RDA, which is higher than rice (Fe 10.6% DV, Zn 16.8% DV, protein 13.4% DV), wheat (Fe 20.6% DV, Zn 8.8% DV, protein 21.1% DV), and maize (Fe 15.9% DV, Zn 22.7% DV, protein 16.7% DV; Longvah et al., 2017; Saleh et al., 2013). Moreover, depending on the amount of little millet consumed daily basis, it can even meet with 100% DV of these important and major nutrients (Anitha et al., 2019). A previous study has shown that little millet can be eaten like rice and can easily replace the staple (Anitha et al., 2019); therefore, it is easy to achieve adequate consumption in staple form.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consumption of little millet could potentially contribute up to 28% Fe, 36.8% Zn, and 27.4% protein of RDA, which is higher than rice (Fe 10.6% DV, Zn 16.8% DV, protein 13.4% DV), wheat (Fe 20.6% DV, Zn 8.8% DV, protein 21.1% DV), and maize (Fe 15.9% DV, Zn 22.7% DV, protein 16.7% DV; Longvah et al., 2017; Saleh et al., 2013). Moreover, depending on the amount of little millet consumed daily basis, it can even meet with 100% DV of these important and major nutrients (Anitha et al., 2019). A previous study has shown that little millet can be eaten like rice and can easily replace the staple (Anitha et al., 2019); therefore, it is easy to achieve adequate consumption in staple form.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, depending on the amount of little millet consumed daily basis, it can even meet with 100% DV of these important and major nutrients (Anitha et al., 2019). A previous study has shown that little millet can be eaten like rice and can easily replace the staple (Anitha et al., 2019); therefore, it is easy to achieve adequate consumption in staple form. The high amount of major nutrients in little millet has the potential to meet the RDA of these major nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…The children and adolescents of the present study and study cited were nutritionally nor-mal. There are Indian studies supporting a modest association of stunting and nutrition (Singh et al 2017;Anitha et al 2019). However, more comprehensive studies and reviews of the association of growth and dietary nutrients concludes clear lack of association between nutrition and growth in height (Devakumar et al 2014;Goudet et al 2017;Pospisil et al 2017;Hermanussen et al 2018a;Hermanussen et al 2018b).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that apart from a sedentary lifestyle and obesity, the type of food consumed plays a key role in diabetes. Main staples such as refined rice, refined wheat and maize contribute up to 80% of the energy intake in developing countries (2). Diversifying food staples and mainstreaming traditional nutritious and less glucogenic staples in the majority of developing countries is very important to manage and prevent diabetes; millets and sorghum figure first in this list of staples.…”
Section: Introductionmentioning
confidence: 99%